PENGOLAHAN MATERIAL LIMBAH BONGGOL JAGUNG SEBAGAI PRODUK AKSESORIS FESYEN - Maghfirah Chairunnisa; Fajar Ciptandi (ATRAT: Jurnal Seni Rupa, 2018)
Indonesia is an agricultural country produces various agricultural. This post-harvest activity of agriculture causes the amount of agricultural waste to be greatly increased. One of the agricultural wastes that increase every year is corncob waste, and one of the cities that produce a lot of corncob waste is Bogor. Corncob waste treatment has begun to develop, which has been processed into handicraft products. However, the processing of corncob waste has not yet developed in fashion’s realm. The research method used is literary studies, surveys and interviews with previous researchers, also observations to know the material under study and continued by making various experiments on assembly techniques and product design of corncob. In this research, corncob waste will be processed into a material suitable for use as a fashion accessory product. This research is focused on developing techniques, form of modules and product design of corncob waste that will be used as fashion accessories products.Keywords: Corncob Waste, Bogor, Fashion Products________________________________________________________________ Indonesia merupakan negara agraris yang menghasilkan beragam hasil pertanian. Kegiatan pascapanen hasil pertanian ini menyebabkan jumlah limbah pertanian yang sangat meningkat. Salah satu limbah pertanian yang meningkat setiap tahunnya adalah limbah bonggol jagung, dan salah satu kota yang menghasilkan banyak limbah bonggol jagung adalah Kota Bogor. Pengolahan limbah bonggol jagung sudah mulai berkembang, yaitu sudah diolah menjadi produk kerajinan. Akan tetapi, pengolahan limbah bonggol jagung belum berkembang dalam ranah fesyen. Metode penelitian yang digunakan adalah studi literartur, survei dan wawancara kepada peneliti sebelumnya, selanjutnya melakukan observasi untuk mengenal material yang diteliti dan dilanjutkan dengan membuat berbagai eksperimen teknik perakitan dan desain produk bonggol jagung. Dalam penelitian ini, limbah bonggol jagung akan diolah menjadi material yang layak digunakan sebagai produk aksesoris fesyen. Penelitian difokuskan pada pengembangan teknik, bentuk modul dan desain produk bonggol jagung yang akan dijadikan produk aksesoris fesyen.Kata Kunci: Limbah Bonggol Jagung, Kota Bogor, Produk Fesyen